A Path Analysis Model Pertinent to Undergraduates’ Academic Success: Examining Academic Confidence, Psychological Capital and Academic Coping Factors - (:unkn) unknown (My University, 2017)
The major purpose of this study was to create a path analysis model of academic success in a group of university students, which included the variables of academic confidence and psychological capital with a mediator variable - academic coping. 400 undergraduates from Marmara University and Istanbul Commerce University who were in sophomore, junior and senior years participated in the study. The Academic Behavioral Confidence Scale, the Academic Coping Strategies Scale and the Psychological Capital Test Battery composed of the Academic Self-Efficacy Scale, the Life Orientation Test, the Hope Scale and the Resilience Scale were utilized to disclose the predictive roles of these variables on academic success. The results of path analyses showed that academic confidence and psychological capital had pivotal direct and indirect effects on academic success via the mediator variable – academic coping. Academic coping had also a direct influence on academic success.  The findings of the study are essential for telling both vocational counselors and educational psychologists the fact that career interventions for university students should consider the non-cognitive factors on their academic achievements.
A Path Analysis Model Pertinent to Undergraduates’ Academic Success